Clinical importance of eflornithine (α-difluoromethylornithine) for the treatment of malignant gliomas. (April 2018) - Levin, Victor A; Ictech, Sandra E; Hess, Kenneth R
This review covers the literature between 1989 and 2007 on studies relevant to the neuro-oncology usage of eflornithine (α-difluoromethylornithine), an oral agent that irreversibly inhibits the enzyme ornithine decarboxylase. It covers the use of eflornithine, alone or in combination, to treat high-grade gliomas. In addition, we provide an update on overall survival from The University of Texas MD Anderson Cancer Center Community Clinical Oncology Program and Clinical Trials Data Office that demonstrates a meaningful benefit in overall survival for eflornithine as a single agent and in combination with nitrosourea-based therapies for anaplastic gliomas. We also provide a framework for understanding the basis and study design of the ongoing pivotal, registrational Phase III multicenter trial for recurrent/progressive anaplastic astrocytoma.